De la forêt à l’assiette, les connaissances traditionnelles sur les champignons comestibles de la communauté P’urhepecha de Cheran K’eri - Tania González Rivadeneira; Arturo Argueta Villamar (Revue d'ethnoécologie)
The mushroom harvesting for the indigenous P'urhepecha is an activity that allows subsistence, especially in the rainy season a period of great diversity, so they have been consumed as food since prehispanic times.The feeding of P'urhepecha communities exemplifies relationships with nature. The life history of fungi is observed in this article from the different moments in which comuneros and fungi interact, thus stablish relationships to the foods throughout cycles shared of life.Traditional ecological knowledge allows us to describe the "path of mushrooms", since they arise like "Terekua sapichu" (Flower of the earth, small or baby) in the forest, until they are consumed and commercialized by the comuneros, as well as also the practices of collection and transformation of fungi.It is concluded that fungi, as food, are related to the comuneros beyond the mere act of preparation and consumption. The ecological knowledge about them has shaped the biocultural landscape of the community and allows the incorporation of "wild" species to a diet very characteristic of the P'urhepecha people.It is concluded that the P'urhepecha relation with the mushrooms, as food, are beyond of the act of preparation and consumption. The ecological knowledge about them has shaped the biocultural landscape of the community and allows the incorporation of "wild" species to a diet very characteristic of the P'urhepecha people.